Cobrança pelo uso dos recursos hídricos do Aquífero Guarani pelos países integrantes do Mercosul à partir da legislação brasileira - Bolzan, Eduardo Augusto Cordeiro (2008)
This work presents as theme the Charging for the Use of Guarani Aquifer Hydric Resources by the Countries Members of Mercosur, taking account the Brazilian legislation. Initially it is presented a short approach to the concern evolution about the scarceness of planet natural resources, especially after the formation of many economic blocs around the world, which gradually and progressively demand more from the environment. After that, the Mercosur analysis starts, with a brief historical digression about all environmental movements that lead to governments awareness about the need of environmental defense, confronting them with the Mercosur constituting acts, and those currently developed in this Latin America region. Subsequently, a meticulous analysis on the importance of freshwater in the world is done, about what is causing its scarcity, and the procedures so far adopted for its preservation, thereby accessing some polemical aspects about this subject, with particularity to the Guarani Aquifer specific point. Finally, are presented the resources made available to the governments in order to make possible the Guarani Aquifer protection, in a shared way in Mercosur, with their main requirements and its viability through taxes, and the impossibility of its taxation by the way described in the intern legislation of the countries members of Mercosur, establishing as initial point the Brazilian legal system.